Analysis Word of Abbreviations Used by Gen Z on Twitter (X): Qualitative Study - Pebriyanti, Valentine; Rosyidah, Rossy Halimatun (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This research discusses the abbreviations of words used on Twitter (X) by Gen Z. This study aims to analyze the categorization and functions of abbreviations used by Generation Z on the Twitter (X) platform. This research is based on theories of Schendl (2001) and Jakobson (1960). The study employs a qualitative descriptive method with a thematic analysis design, analyzing screenshot-based textual data. The findings indicate that the dominant type of abbreviation is Initialism, totalling 20 instances, which is defined as an abbreviation where each letter is pronounced separately. This is followed by Clipping, which consists of 10 instances and refers to a shortened form of a word. Blends recorded the same frequency, 10 instances, referring to words formed by combining two or more words. Next, Acronyms appeared 7 instances, defined as abbreviations pronounced as regular words. Lastly, Contractions were found in 3 instances, referring to two words combined into one using an apostrophe (’). This study not only identifies patterns of digital language development among Generation Z but also contributes academically to current digital linguistics studies. These findings enrich our understanding of how social media communication practices influence language change, especially in the use of word abbreviations. In addition, this study has significant social implications, particularly in efforts to improve digital literacy and to design communication strategies better suited to the characteristics of the younger generation in the technological era.